Potencial de revestimentos comestíveis à base de quitosana e extrato de própolis na conservação do camarão branco do pacífico (litopenaeus vannamei) - Souza, Joice Teixeira (2021)
The scope of this study was to obtain and characterize edible films and coatings based on chitosan combined with different concentrations of green and red propolis extract and to evaluate the potential of the coatings on the quality of chilled and frozen white shrimp (Litopenaeus vannamei). The films produced with different concentrations of green and red propolis extract (0.12%, 0.25%, 0.50%, 1.0% and 2.0%) were characterized in terms of their optical properties: color and opacity; barrier properties: water vapor permeability and solubility; mechanical properties: tensile strength, elongation at break and modulus of elasticity and scanning electron microscopy - SEM. The antimicrobial activity of filmogenic solutions was evaluated against standard strains of Salmonella typhimurium, Escherichia coli and Staphylococcus aureus. For the chilled shrimp experiment, the samples were subjected to different treatments and divided into five groups: Control (C); Metabisulfite (MBS); Chitosan (Q); Green propolis extract (EPVD) and Chitosan + green propolis extract (QEPVD), afterwards, it was stored refrigerated at 4 ± 1 ºC for 12 days. For the frozen shrimp experiment, the shrimp was processed and divided into: Control (C); Glacier (G), Chitosan (Q); Chitosan + green propolis extract (QEPVD) and chitosan + red propolis extract (QEPVM) after application of the treatments was stored frozen at - 18 ºC for 180 days. To assess the quality of chilled and frozen shrimp, the groups were subjected to physical-chemical analyzes: hydrogen potential - pH, reaction to substances reactive to thiobarbituric acid - TBARS, weight loss by cooking - PPC, water retention capacity - CRA , texture and instrumental color, microbiological analysis to determine the presence of Salmonella spp. in the initial time, count of Staphylococcus aureus and Escherichia coli, total count of psychrotrophic and aerobic mesophilic bacteria, in the experiment with chilled shrimp the analysis of the Quality Index Method - MIQ was also performed. According to the data obtained, a significant difference (p <0.05) was observed in the barrier and mechanical properties of the films and better results were found in films with concentrations of 0.12 and 0.25% of green and red propolis extract. The incorporation of the propolis extract to chitosan provided better results of antimicrobial activity against the E. coli strain. The 1.5% chitosan coating solution with 0.25% green propolis extract and 1.5% chitosan with 0.25% red propolis extract were chosen for the continuation of the study due to the positive results found in the previous analyzes. In the experiment with the chilled shrimp, it was observed that the shrimp samples coated with the combination of chitosan and propolis extract showed better results in terms of pH, TBARS, texture and inhibition of microbial and melanosis development. In the experiment with frozen shrimp, inhibition of the development of microorganisms was observed, oxidative stability, pH maintenance and better results in water retention capacity and weight maintenance. From the data obtained, it is possible to infer that there was a synergy between chitosan and the propolis extract and, therefore, this combination has potential as an edible coating and natural preservative to increase the sensory quality and useful life of white shrimp